The effect of the body mechanic behaviors on the low back pain - Aynur Uysal Toraman; Melek Ardahan; Özüm Erkin Balyacı (Tehran University of Medical Sciences, 2015)
Background & Aim: Low back pain (LBP) has developed as a major public health problem in the western industrialized societies, and the socio-economic burden of this problem has a huge dimension. The aim of this study was to investigate the effect of body mechanics behavior on LBP of workers.| Methods & Materials: Descriptive study includes convenience sample of 290 workers who work at car production industry. The research data were collected using: (1) The worker's sociodemographic data form, (2) the body mechanics behaviors form, and (3) Oswestry Disability Index (ODI) by the researchers. Results: About 90% of the workers are male, 74.8% of them are married, and 36.9% of them are high school graduates. In about 48.3% of the workers the pain recurrence was very mild, in 24.8% of them was moderate, and in 10.3% of them was mild and did not varied much. A significant difference has been determined between ODI classification and paying attention to the position of spine, while lifting something (P < 0.01), paying attention to the position of head, shoulder and back, while walking (P < 0.05), paying attention to suitable sitting position (P < 0.05). Conclusion: Workers LBP complaints varied. Complaints were found "minimally disability" to "crippled" on ODI classification. It is clear that body mechanic behaviors of the workers have an influence on ODI.